Before digital, return to the sources: communicators, media and discourse - Villanueva, Eduardo (2016)
With mounting criticisms on the relevance of communication studies, both to train future professionals as well as for academic enquiry, and with the influx of changes coming from society’s digital transformations, a review of the different interaction between the professional and technical aspects that constitute the field allow for elucidation of the actual specificity of the discipline or set of disciplines that are grouped under the banner of “communication sciences” or “media studies”. This essay strives to propose an understanding of these interactions through an specific metaphor, and then how this understanding can be used to facilitate academic thinking and professional undertakings cross-dialog.